Firm Size, Life Cycle Dynamics and Growth Constraints : Evidence from Mexico - Saborowski, Christian (IMF Working Papers; Working Paper ;, 2019)
This paper examines the variation in life cycle growth across the universe of Mexican firms. We establish two stylized facts to motivate our analysis: first, we show that firm size matters for development by illustrating a close correlation with state-level per capita incomes. Second, we show that few firms grow as much as their U.S. peers while the majority stagnates at less than twice their initial size. To gain insights into the distinguishing characteristics of the two groups, we then econometrically decompose life cycle growth across firms. We find that firms that have financial access and multiple establishments and that are formal, part of diversified industries and located in population centers can grow at sizeable rates.